MARKETING MIX STRATEGY OF ACEH FOREST KELULUT HONEY IN NORTH ACEH DISTRICT - Halida Bahri; Agustinawati; Samsidar (RADJA PUBLIKA, 2025)
The main objective of this study is to describe and formulate a promotional strategy method carried out by the Aceh Forest Kelulut Honey Farming Group in North Aceh Regency. The method used in this study is descriptive qualitative, the researcher wants to see how the marketing promotion strategy of Aceh Forest Kelulut Honey in North Aceh Regency is using the marketing mix theory, namely product, price, promotion, distribution (place). The results of the study show that Aceh Forest uses the Shopee e-commerce platform and promotions via social media TikTok, Instagram, YouTube and uses advertising endorsement services from one of Aceh's local artists in marketing Kelulut honey to its consumers. Aceh Forest also provides resellers in shops and pharmacies in Lhokseumawe, North Aceh, Bireun, and Banda Aceh.